Expectancy to Eat Modulates Cognitive Control and Attention Toward Irrelevant Food and Non-food Images in Healthy Starving Individuals. A Behavioral Study - Schiff, Sami; Testa, Giulia; Rusconi, Maria Luisa; Angeli, Paolo; Mapelli, Daniela (Frontiers in Psychology, 2021)
It is thought that just as hunger itself, the expectancy to eat impacts attention and cognitive control toward food stimuli, but this theory has not been extensively explored at a behavioral level. In order to study the effect of expectancy to eat on attentional and cognitive control mechanisms, 63 healthy fasting participants were presented with an affective priming spatial compatibility Simon task that included both food and object (non-food) distracters. The participants (N = 63) were randomly assigned to two groups: an “immediate expectancy” group made up of participants who expected to eat immediately after the task (N = 31; females = 21; age = 26.8 ± 9.6) and a “delayed expectancy” cohort made up of individuals who expected to eat a few hours later (N = 32; females = 21; age = 25.0 ± 8.0). Slower reaction times (RTs) toward the food and non-food distracters and a more pronounced effect on the RTs in the incompatible condition [i.e., the Simon effect (SE)] were noted in both groups. The effect of the food and non-food distracters on the RTs was more pronounced in the immediate with respect to the delayed expectancy group. The magnitude of the SE for the food and the non-food distracters was also greater in the immediate with respect to the delayed expectancy group. These results seem to indicate that when the expectancy to eat is short, the RTs are delayed, and the SE is more pronounced when food and non-food distracters are presented. Instead, when the expectancy to eat is more distant, the distracters have less of an effect on the RTs and the correspondence effect is smaller. Our results suggest that the expectancy to eat can modulate both attention orienting and cognitive control mechanisms in healthy fasting individuals when distracting details are competing with information processing during goal directed behavior.